Van der Pol systems with various restoring elements - Dinh, Nguyen Van; Chi, Tran Kim (Vietnam Journal of Mechanics, 2006)
Van der Pol oscillators with various linear and cubic restoring elements are examined. The evolution of stationary self-excited oscillations is described and the role of self-excitation as that of restoring elements is shown. Numerical method on computer is used.